Peningkatan Kemampuan Membaca Pemahaman dengan Menggunakan Strategi PORPE pada Siswa Kelas IV SD - Yulis, Rahma; Amini, Risda; Mahyuddin, Ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to describe the improvement of reading comprehension ability by using the PORPE strategy on the 4th grade students of Elementary School No.34 Simpang Haru, Padang. Research subjects were teachers and 32 students in the 4th grade of Elementary School No. 34 Simpang Haru, Padang. This study is a classroom action research that uses qualitative and quantitative approaches. The results showed that the students’ ability in reading comprehension increased from 82,4 (Good) with 78,1% level of mastery in cycle I, to 90 (Very Good) with 95% level of mastery in cycle II. The percentage of improvement from cycle I to cycle II is 7,6 %. Based on these results, it is concluded that the PORPE strategy can improve the ability of reading comprehension of the 4th grade students of Elementary School.